Exploring the patient experience of living with a peripherally inserted central catheter (PICC): A pilot study - Cooper, A.; Kelly, C.; Brown, Janie (2017)
Background: Peripherally inserted central catheters (PICCs) are used to administer chemotherapy to oncology patients. A review o f the literature revealed a gap in the understanding o f the patient experience o f living with a PICC. Aim: To explore patient experience and satisfaction including self-reported adverse events o f PICC use. Methods: A prospective survey was utilised to gain an understanding o f patients' experiences o f living with PICCs. The survey included self-reported pain, comfort and ease o f managing activities o f daily living. Participants were surveyed at two time points over one month. Results: The positive aspects of PICCs included ease o f treatment and little pain being associated with the PICC site. However, PICCs did hinder patients in a number of activities including work, leisure and exercise. Discussion: Little research has been conducted exploring patient experience o f living with a PICC. This small pilot study identifies areas that warrant further investigation to assist with providing patient centred holistic care.